Quaid-i-Azam Mohammad Ali Jinnah : His Personality and His Politics - Burke, S. M.; Quraishi, Salim Al-Din (Karachi Oxford University Press, 1997)
This volume shows that it was not Quaid-i-Azam Mohammad Ali Jinnah, but Mahatma Gandhi who introduced religion into politics. Congress policies under Gandhi drove the Hindus and the Muslims. And they eventually convinced Jinnah, who had long fought for Hindu-Muslim unity, that his dream of a united India was nothing but a mirage.
Include Note, Bibliography and Index.
Keywords: Statesmen -- Pakistan -- Jinnah, Mahomed Ali, 1876-1948